Improving Students’ Learning Achievements Through Lesson Study: Implementation of the Merdeka Curriculum - Mira Tania (Darussalam English Journal (DEJ), 2023)
This research aimed at analyzing the implementation of lesson study to improve the Seventh Grade Students’ learning achievements within the implication of the Merdeka Curriculum. This research was a classroom action research (CAR).and 26 students used as samples. To get the data, the researcher used Test. To analyze the data, the researcher used descriptive analysis. The results showed that the learning achievements of the Seventh Grade students of Islamic Integrated School of SMP Harapan Mulia Palembang had improved. It was proved by the learning achievements scores obtained during Cycle 1 and Cycle 2. In other words, in Cycle 1, it was found out that the total was 1550, mean score was 70, comprehensive ability was 70%, and learning completion was 75%) while in cycle 2, the total was 1780, mean score was 85, comprehensive ability was 85%, and learning completion was 98% It means that the average of comprehensive ability was 15% and learning completion had increased by 23%.. In conclusion, the implementation of lesson study could improve the learning achievements of the Seventh Grade Students of Islamic Integrated School of SMP Harapan Mulia Palembang.